Engajamento disciplinar produtivo e práticas epistêmicas: construtos para avaliação da aprendizagem em uma atividade sobre drogas no ensino médio - Sarah Eliane de Matos Silva (2023)
The objective of the study was to understand the relationships between the discursive interactions fostered by a didactic sequence on drug use in adolescence and its psychosocial repercussions and the strategies used by the teacher to mediate these interactions. Additionally, we analyze the Productive Disciplinary Engagement (EDP) and related practices, based on the transcription of the dialogue of students from a state public school in Minas Gerais on socio-scientific issues. Through participant observation and audiovisual recordings of a group activity, we perceive discursive processes that show the epistemic practices of production, communication, evaluation and legitimation of knowledge. Additionally, we noticed a pattern of engagement indicators — E3 (presence of emotional characteristics related to actions to solve the problem), EDP1 (discussion about the sophistication of ideas and construction of explanatory relationships) and EDP2 (there is collaborative work in the construction of the explanation and recognition of limits in its applications) — which can be explained due to the transposition of the social norms of scientific knowledge (forum, public standards of analysis, receptivity to criticism and moderate equality) to the classroom. The data indicate that these norms provided discursive practices among students and also the construction of understandings through social interactions. Bearing in mind that indicators E3, EDP1 and EDP2 occurred in all episodes and that the criterion used to define these episodes was the knowledge legitimized by students during the group activity, we suggest a relationship between these indicators of engagement and epistemic practice of legitimizing knowledge. We observed that the discussion of socio-scientific issues fostered investigative work and student involvement in the didactic activity. We therefore propose a model that represents investigative science teaching, permeated by socio-scientific debate; and that values activities for proposing and legitimizing ideas in the classroom, promoting dialogue and mobilization of the domains of scientific knowledge (epistemic, social, material and conceptual). It was evident in this study, therefore, that teaching mediated by socio-scientific issues (use of psychotropic substances in adolescence and its psychosocial repercussions) was a didactic approach that facilitated the appropriation of epistemic practices and the engagement of students in science classes.